2013
DOI: 10.1007/s00590-012-1155-0
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of external fixation versus volar locking plate in the treatment of unstable intra-articular distal radius fractures

Abstract: The aim of this study is to compare the radiological and functional outcomes of open reduction and volar locking plates versus external fixation (EF) in the treatment of unstable intra-articular distal radius fractures. In this retrospective comparative study, 69 of 80 patients who underwent an operation for AO/ASIF C1, C2 and C3 distal radius fractures were assessed. Functional evaluation was performed using the Gartland-Werley scoring system and the PRWE scale, and wrist range of motion and grip strength was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
3
37
2
1
Order By: Relevance
“…A higher incidence of infection was noted in the EF group, in which 11/41 (27%) patients treated with EF developed a pin Significant p values are shown in bold tract infection that required oral antibiotic treatment versus 1/28 (4%) patients in the VLP group. The overall complication and infection rates of the EF group were higher in our study than in others [14,19,21,22]. Navarro et al [20] demonstrated that the total complication rate was equal between the EF and VLP groups.…”
Section: Discussioncontrasting
confidence: 61%
“…A higher incidence of infection was noted in the EF group, in which 11/41 (27%) patients treated with EF developed a pin Significant p values are shown in bold tract infection that required oral antibiotic treatment versus 1/28 (4%) patients in the VLP group. The overall complication and infection rates of the EF group were higher in our study than in others [14,19,21,22]. Navarro et al [20] demonstrated that the total complication rate was equal between the EF and VLP groups.…”
Section: Discussioncontrasting
confidence: 61%
“…The higher infection rate is not unexpected, given that pin tract infections are one of the known disadvantages to ExFix and a primary limitation to time to hardware removal. [12][13][14][15][16][17] Despite the differences in complication rates in infection, hardware failure, and complex regional pain syndrome, there was no difference in unplanned reoperations between the two groups. The majority of pin tract infections can be successfully treated with antibiotics; ultimately, only two patients from the external fixator group required a secondary irrigation and debridement operation for infection.…”
Section: Discussionmentioning
confidence: 93%
“…Higher rates of neuritis, implant failure, and infection have been recorded for EF, while tendon complications and early implant removal have been observed more frequently with VP in the studies by Jorge-Mora et al and Margaliot [24,26]. Leung et al found a lower rate of secondary osteoarthritis [27] and Kumbaraci et al [11] a lower complication rate overall in the VP group. However, similar total complication rates were reported by Navarro et al [21] and Shukla et al [17] for both methods.…”
Section: Complication Ratesmentioning
confidence: 98%
“…Anatomic reduction and stable fixation of displaced intraarticular distal radius fractures are difficult to obtain, and poor outcomes are common [7][8][9][10]. Various surgical procedures have been described, but stabilization with a volar locking plate or an external fixator with additional K-wires are commonly used techniques [7,[10][11][12][13][14]. Although these two methods have been previously compared in the literature, their distinct advantages and disadvantages have not been clearly established so far [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%